Is transit-oriented development (TOD) an internationally transferable policy concept? - Thomas, Ren; Pojani, Dorina; Lenferink, Sander; Bertolini, Luca; Stead, Dominic; van der Krabben, Erwin (Regional studies, 2018)
Many cities and regions have embraced the concept of transit-oriented development (TOD). This paper explores how transfer of TOD as a policy concept impacts its implementation in the Netherlands. The study determined international policy ideas and tools that have contributed to implementation and tested them with Dutch experts using workshops, serious gaming and design charrettes. The findings suggest a number of factors complicating policy transfer, and that 'softer' transferable lessons (e.g., good actor relationships, information sharing) are much more difficult to transfer than 'harder' technical tools. Using policy lessons and tools in learning exercises helps to develop contextually appropriate policy solutions.